Tension Hemothorax in Aortic Rupture: A Case Report - Pometlová, Jana; Madeja, Roman; Demel, Jiří; Ječmínková, Renata; Procházka, Václav; Kitka, Miroslav; Pleva, Leopold (Medicina, 2021)
Background: The standard ATLS protocol calls for chest drain insertion in patients with hemothorax before performing further diagnostic steps. However, if trauma-induced thoracic aortic rupture is the underlying cause, such drainage can lead to massive bleeding and death of the patient. Case report: This report describes a case of a polytrauma patient (car accident), aged 21, with symmetrical chest and decreased breath sounds dorsally on the left. An urgent CT scan revealed subadventitial Grade III thoracic aortic transection with mediastinal hematoma, a massive left-sided hemothorax with mediastinal shift to the right, and other injuries. Stent-graft implantation with subsequent left hemithorax drainage was urgently performed, during which the patient became increasingly unstable from the circulatory point of view. This traumatic hemorrhagic shock was successfully managed at the ICU. Conclusion: Although hemothorax is a serious condition requiring rapid treatment, the knowledge of its origin is of utmost importance; performing chest drainage without bleeding control can lead to circulatory instability and death of the patient. Hence, where aortic injury can be suspected based on the mechanism of the injury, it is beneficial to perform spiral CT angiography for accurate diagnosis first and, in cases of aortic injury, to control the bleeding prior to drainage.
Keywords: Hemothorax; ruptura aorty; Humans; lidé; Aortic Rupture; hemotorax; Tomography, X-Ray Computed; počítačová rentgenová tomografie